Monolayer films from poly(lactic acid) PLA/poly(3-hydroxybutyrate-co-hydroxyvalerate) PHBV blends for food packaging applications - Hosein Pouriman; Kevin Graham; Krishnan Jayaraman (eXPRESS Polymer Letters, 2023)
Four out of twelve different formulations consisting of poly(lactic acid) (PLA), poly(3-hydroxybutyrate-co-hydroxyvalerate) (PHBV), triethyl citrate (TC), and epoxy-functionalized styrene acrylate (ESA) components were selected based on their superior elongation at break, rheological properties, and composition range from other batches. Each batch was made into a monolayer thin film via a blown film extrusion process. The films’ mechanical, oxygen gas, and moisture barrier and aesthetic properties were measured. The findings paved the understanding for developing biodegradable packaging to extend the shelf life of oxygen and moisture-sensitive food products. The results proved the significance of systematic analysis of the interacting effects of components’ mixing ratios on different properties of the blend. The produced films’ oxygen gas and moisture barrier properties showed significant improvement compared to neat PLA; however, still more than neat PHBV.